2015
DOI: 10.4314/ijbcs.v8i4.31
|View full text |Cite
|
Sign up to set email alerts
|

Diversité agro-morphologique des accessions de fonio [<i>Digitaria exilis</i> (Kippist.) Stapf.] au Niger

Abstract: La variablité morphologique de 67 accessions de fonio [Digitaria exilis (Kippist.) Stapf.] collectées au Niger a été évaluée au cours de deux années (2011 et 2012). Seize (16) caractères agro morphologiques (dont 14 caractères quantitatifs et 2 caractères qualitatifs) ont été évalués en station dans deux zones agroécologiques différentes (Tarna en zone sahélo-saharienne et Tara en zone soudanienne). La classification acsendante hierarchique (CAH) et l'analyse factorielle discriminante (AFD) ont mis en évidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
3
8
0
1
Order By: Relevance
“…Such observations were described by certain authors on others species cultivated in West Africa (Bakasso, 2010;Missihoun et al, 2012, Saïdou et al, 2014. In the same way the racial diversity of the millet local cultivars collected through the classes comes to confirm not only the ways of exchanges between ZAE but also between the close countries like Nigeria, Burkina Faso, Niger and Togo.…”
Section: Figure 6 Distribution Of Racial Diversity Within Morphologicsupporting
confidence: 50%
“…Such observations were described by certain authors on others species cultivated in West Africa (Bakasso, 2010;Missihoun et al, 2012, Saïdou et al, 2014. In the same way the racial diversity of the millet local cultivars collected through the classes comes to confirm not only the ways of exchanges between ZAE but also between the close countries like Nigeria, Burkina Faso, Niger and Togo.…”
Section: Figure 6 Distribution Of Racial Diversity Within Morphologicsupporting
confidence: 50%
“…Even though these type of markers may present a low level of polymorphism, heritability, and expression and are often susceptible to phenotypic plasticity [12], they were used by many authors to study agro morphological diversity in other small grain cereals [13][14][15][16]. Various studies reported the existence of a wide range of diversity in fonio germplasm accessions [17][18][19][20][21] for quantitative traits (plant height, number of leaves per plant, internode length, days to 50% flowering, days to 50% maturity, leaf width, panicle leaf length, stem girth, raceme length, dry biomass yield and grain yield, seeds size, thousand seed weight) and for qualitative traits (collar color, green color of foliar limb, anthocyanin coloration and distribution in different aerial organs, type of panicle and panicle exertion, and grain color). However, previous works on fonio agromorphological characterization limited their collection area to only one or two countries, or used few accessions, overlooking the wider distribution range of the crop.…”
Section: Introductionmentioning
confidence: 99%
“…Cela témoigne que chez les cocotiers Grand le polymorphisme des caractères qualitatifs est fonction de la population surtout que d'après Konan et al (2007a) le niveau d'hétérozygotie est variable chez ces populations qui sont allogames. Egalement, sur le karité (Diarrassouba et al, 2009), le figuier (Aljane et Ferchichi, 2014) et le fonio (Saidou et al, 2014) les caractères qualitatifs ont été utilisés pour révéler la variabilité phénotypique. En se basant sur des caractères qualitatifs tels que la catégorie du bulbe, la forme du fruit et la couleur du fruit immature, des populations de cocotier Grand ont été collectées dans les îles Andaman et Nicobar par le National Bureau of Plant Genetic Resources (NBPGR) pour être conservées en Inde (Abraham et al, 2008).…”
Section: Discussionunclassified